Surfaces resistant to fouling from biological fluids: towards bioactive surfaces for real applications - Rodriguez-Emmenegger, Cesar; Houska, Milan; Alles, Aldo Bologna; Brynda, Eduard (Macromolecular bioscience, 2012)
The fouling from four human body fluids - blood plasma, cerebrospinal fluid, urine and saliva - and four animal fluids - foetal bovine and calf sera, egg and milk - relevant to human and veterinary medicine, immunology, biology and diagnostics is assessed on antifouling SAMs and on polymer brushes of oligo(ethylene glycol) methacrylate, 2-hydroxyethyl methacrylate, carboxybetaine acrylamide and N-(2-hydroxypropyl)methacrylamide synthesized via ATRP. While important deposits from the all biofluids are observed on SAMs, a superior resistance is achieved on polymer brushes. Importantly, only poly(CBAA) and poly(HPMA) are capable of resisting the fouling from the most challenging media, blood plasma and eggs.
Keywords: akrylové pryskyřice; mléko; spektroskopie infračervená s Fourierovou transformací; Bacteria; dezinficiencia; povrchové vlastnosti; Acrylic Resins; Disinfectants; Eggs; Body Fluids; skot; tělesné tekutiny; Surface Properties; Spectroscopy, Fourier Transform Infrared; zvířata; Humans; Cattle; Milk; Coated Materials, Biocompatible; biokompatibilní potahované materiály; vejce; lidé; Animals